Implications of cancer stem cells in developing therapeutic resistance in oral cancer. (November 2016) - Naik, Prajna Paramita; Das, Durgesh Nandini; Panda, Prashanta Kumar; Mukhopadhyay, Subhadip; Sinha, Niharika; Praharaj, Prakash Priyadarshi; Agarwal, Rajesh; Bhutia, Sujit Kumar
Highlights: The CSCs in oral cancer is associated with chemo-radio-resistance. Abrupt developmental signaling, apoptosis and autophagy promotes CSC survival. Cell cycle regulation and enhanced DNA damage repair protects CSC from therapies. Altered drug response and niche remodeling defends CSC from chemo-radio agents. EMT, low ROS and epigenetic and metabolic reprogramming induces regimen resistance. Abstract: Conventional therapeutics are often frequented with recurrences, refraction and regimen resistance in oral cavity cancers which are predominantly manifested by cancer stem cells (CSCs). During oncoevolution, cancer cells may undergo structural and functional reprogramming wherein they evolve as highly tolerant CSC phenotypes with greater survival advantages. The CSCs possess inherent and exclusive properties including self-renewal, hierarchical differentiation, and tumorigenicity that serve as the basis of chemo-radio-resistance in oral cancer. However, the key mechanisms underlying the CSC-mediated therapy resistance need to be further elucidated. A spectrum of dysfunctional cellular pathways including the developmental signaling, apoptosis, autophagy, cell cycle regulation, DNA damage responses and epigenetic regulations protect the CSCs from conventional therapies. Moreover, tumor niche shelters CSCs and creates an immunosuppressive environment favoring the survival of CSCs. Maintenance of lower redox status, epithelial-to-mesenchymal transition (EMT), metabolic reprogramming and altered drug responses are the accessory features that aid in the process of chemo-radio-resistance in oral CSCs. This review deals with the functional and molecular basis of cancer cell pluripotency-associated resistance highlighting the abrupt fundamental cellular processes; targeting these events may hold a great promise in the successful treatment of oral cancer.